Adoption of Digital Micro Wakaf Bank by Ultra-Micro and Micro Businesses in Indonesia - Dewi sartika Nasution; Intan Kusuma Pratiwi; Dahruji (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Micro, small, and medium enterprises (MSMEs) are the backbone of the economy of Indonesia. Despite that fact, ultra-micro and micro entrepreneurs still face several constraints. Micro Waqf Bank (MWB) is one solution that utilizes Islamic social funds. This solution develops digital financial services to expand access to financing, efficiency of services, and business development. The limited study of ultra-micro and micro-entrepreneurs’ adoption of MWB’s digitalization makes this research important. Method: This research uses a mixed-methods approach, combining quantitative and qualitative methods. In this research, a sequential/stepwise mixed-methods strategy was used, with a sequential exploratory design. The analysis technique used in this research is a qualitative descriptive analysis technique, or what is usually called explanation making, namely, by using data analysis methods and describing the results of interview observations to find out in depth about the adoption of digital MWBs in the 5 MWBs. The quantitative method data analysis technique used by researchers uses the Partial Least Squares (PLS) method with SmartPLS software. Results: The research results show that there are several obstacles that prevent the use of the MWB mobile from being used comprehensively. However, the intention of ultramicro and micro business actors who are BMW customers to use and adopt the BMW application or other digital BMWs as a means of payment transactions and personal and business development for business actors is quite good. Conclusion: This study shows that the use of mobile MWB has not yet reached its full potential due to various challenges in its implementation and adoption. However, ultra-micro and micro business owners as MWB customers demonstrate a strong interest in using MWB’s digital services for transactions, business development, and capacity building. These findings highlight the importance of enhancing usability, aligning with the needs of MSMEs, and ensuring transaction security to increase the adoption of MWB’s digital services.